Pengaruh Kualitas Pelayanan Terhadap Kepuasan Nasabah Pembiayaan Kredit Usaha Rakyat (KUR) Pada Bank Syariah Indonesia (BSI) Kantor Cabang Pembantu (KCP) Paser Tanah Grogot - Achmad Aprianor Firdaus; Karlina Karlina; Nur Azizah Lela (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2023)
The aim of this thesis is to determine the influence of service quality on customer satisfaction with People's Business Credit (KUR) financing at Bank Syariah Indonesia Sub-Branch Office (KCP) Paser Tanah Grogot. Based on the Validity Test which contains 26 statement items, it is declared valid, because rcount > rtable, with an rtable value of 0.3120. The results of the Reliability Test which contains 26 statement items are declared reliable, because the Cronbach alpha value is greater than 0.6 then the Multiple Linear Regression Equation which contains the value of each variable is Y = 1.488 - 0.001X1 + 0.313X2 - 0.035X3 - 0.216X4 + 0.560X5. Based on the Correlation Coefficient Test (R), it shows a value of 0.760 and is in the Coefficient interval 0.60 – 0.799, which means there is a strong influence between Direct Evidence (X1), Reliability (X2), Responsiveness (X3), Assurance (X4) and Empathy (X5) on KUR Financing Customer Satisfaction (Y). The results of the Adjusted R Square Determination Coefficient (R2a) show a value of 0.515 or 51.5%, which means that Direct Evidence (X1), Reliability (X2), Responsiveness (X3), Assurance (X4) and Empathy (X5) provide a percentage contribution or the contribution that influences the KUR Financing Customer Satisfaction variable (Y) at Bank Syariah Indonesia KCP Paser Tanah Grogot is 51.5% while the remaining 48.5% is contributed by other variables not included in this research. The results of the F test calculation analysis (simultaneous) obtained an Fcount value of 9.295 and Ftable using a significance level of 0.000 while the Ftable value was 2.49. So Fcount is 9.295 > Ftable value is 2.49 and the hypothesis test is accepted because there is a significant influence on KUR Financing Customer Satisfaction. The results of the t test calculation analysis show that the t value of the Reliability variable (X2) is 3.341 with a significant level of 0.002, Empathy (X5) is 4.017 with a significant level of 0.000 which has an influence on KUR Financing Customer Satisfaction (Y). Meanwhile, the t-calculated value of Direct Evidence (X1) is -0.007 with a significant level of 0.995, Responsiveness (X3) is -0.187 with a significant level of 0.853, and Guarantee (X4) is -1.819 with a significant level of 0.078 and has no effect on KUR Financing Customer Satisfaction (Y). Based on the calculations above, the Empathy variable (X5) has a dominant influence on KUR Financing Customer Satisfaction (Y) with a t value of 4.017 with a significance level of 0.000. Thus, the second hypothesis in Chapter II which states that the Guarantee variable (X4) has a dominant influence on KUR Financing Customer Satisfaction (Y) is not proven correct (H0 is accepted Ha is rejected).